Analisis Kinerja Turbin Gas pada Pembangkit Listrik Tenaga Gas Unit 4 di PT PLN Indonesia Power Bali PGU - Rahmaniar, Syafira; Bambang Puguh M; Indriyani, Indriyani (Fakultas Teknik UMRI, 2024)
This research discusses the comparison of gas turbine performance in ideal and actual conditions at PLTG unit 4 at PT PLN Indonesia Power Bali PGU. The performance of a gas turbine can be seen from the network and thermal efficiency of the cycle produced. Ideal conditions are the expected conditions, while actual conditions are conditions where a component works in actual conditions. Based on research conducted, the ideal efficiency value is 43.04%, while the actual efficiency value is only 18.23%. The turbine work values ​​in ideal conditions (Ẇts) and ideal efficiency (ηths) have greater values ​​than the actual turbine work (Ẇt) and actual efficiency (ηth). Meanwhile, the ideal fuel consumption (SFC) value is lower/more economical, namely 0.16372 kg/kWh compared to actual fuel consumption (SFC), namely 0.4912 kg/kWh. This difference is caused by isentropic conditions when the turbine is working, some of the heat energy entering the turbine is not utilized due to friction between the parts in the turbine or vibration which is a source of irreversibility in the turbine.